High-Frequency Market Making to Large Institutional Trades. (21st July 2018) - Korajczyk, Robert A; Murphy, Dermot
Abstract: We study market-making high-frequency trader (HFT) dynamics around large institutional trades in Canadian equities markets using order-level data with masked trader identification. Following a regulatory change that negatively affected HFT order activity, we find that bid-ask spreads increased and price impact decreased for institutional trades. The decrease in price impact is strongest for informed institutional traders. During institutional trade executions, HFTs submit more same-direction orders and increase their inventory mean reversion rates. Our evidence indicates that high-frequency trading is associated with lower transaction costs for small, uninformed trades and higher transaction costs for large, informed trades. Received May 24, 2016; editorial decision June 21, 2018 by Editor Andrew Karolyi. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.